2D:4D ratios as an indicator of intrauterine androgen exposure in children who stutter. (August 2019) - Yuksel, Tugba; Sizer, Esra; Durak, Hasan
Abstract: Aim: We aimed to explore whether there is a relationship between stuttering and digit ratio (2D:4D), which is thought to be a marker of prenatal testosterone exposure. Methods: We evaluated a total of 90 children who stutter (CWS; n = 40 mild-to-moderate and n = 50 severe stutters) and 40 healthy peers (CWNS) as controls. We used the Clinical Global Impression–Severity (CGIS) scale to measure the severity of stuttering. We measured the lengths of index finger (2D) and ring finger (4D) of both hands directly and divided to calculate 2D:4D ratio. The difference between the right and the left hand 2D:4D ratio (DR-L ) was also calculated. Result: Significant difference was found in right 2D:4D and the mean DR-L between the CWS and CWNS groups. Right 2D:4D was significantly lower in stuttering boys than in control boys, and in stuttering girls than control girls. Also, DR-L was significantly lower in stuttering boys than control boys. In ANOVA, there were significant differences between the mild-to-moderate, severe stuttering and control groups in terms of right 2D:4D and DR-L . Right hand 2D:4D and DR-L decreased from controls to severe stutterers. Conclusion: Our results suggest that lower right 2D:4D and DR-L were related to the presence and severity of stuttering in children, i.e. CWS had lower 2D:4D and DR-L than CWNS. Further large-scale prospective studies are needed to clarify the reliability of 2D:4D ratio as an indicator of fetal sex hormone exposure level and its relation with the presence and severity of stuttering in children. Highlights: It is not known exactly why stuttering is more common in boys than girls. Prenatal testosterone exposure may play a role in the etiology and chronicity of stuttering in children. The 2D:4D ratio is a newly defined surrogate marker suggested to be associated with prenatal testosterone exposure. We aimed to compare the 2D:4D ratio between children who stutter (CWS) and who do not (CWNS). According to our results CWS had significantly lower right hand 2D:4D ratio than that of CWNS, whereas stuttering boys and girls had similar 2D:4D ratios. Stuttering boys and girls had lower right hand 2D:4D ratio than that of healthy ones.